Effect of densification parameters on the properties of maize residue pellets - Thanasit Wongsiriamnuay (2018)
© 2015 IAgrE. The effect of the conditioning process parameters on the properties of the pellets was investigated. Maize residues were collected locally from the field and crushed into small sizes, dried, and separated for compaction. The effects of the variation of the die temperature (30-80 °C), the compaction pressure (150-250 MPa), and the biomass type (cob, husk, and stalk) on compact density, relaxed density, and durability index were investigated. It was found that the compact density increased with pressure and temperature to around 950-1100% higher than the residue density. The relaxed density was stable at 60-80 °C, but at 30 °C, it was found to decrease from 800-1000 kg m-3to 660-700 kg m-3. The durability index was observed to improve with increasing pressure and temperature by 30-60% and 70-90%, respectively. This corresponded well with the lignin glass transition temperatures being in the range of 60-80 °C at moderate pressure values between 150 MPa and 250 MPa. Pellet density was also found to increase with increasing compression pressure and temperature. Pellet density was three times higher than bulk density and similar to the particle density. Heating the feed materials during compression decreased the compaction pressure from 250 MPa to 150 MPa, resulting in the formation of pellets with a higher durability index and more stable relaxed density.